Incident Comorbidity, Resource Use, and All-Cause Mortality Associated with Prurigo Nodularis: A United Kingdom Retrospective Database Analysis - Christopher Ll Morgan; Melissa Thomas; Benjamin R. Heywood; Sonja Ständer; Shawn G. Kwatra; Zarif K. Jabbar-Lopez; Christophe Piketty; Sylvie Gabriel; Jorge Puelles (Elsevier, 2023)
We described comorbidity, resource utilization, and mortality for patients with prurigo nodularis (PN) using data from the Clinical Practice Research Datalink. Patients with incident PN (2008-2018) were selected and matched to controls. Of 2,416 patients with PN, 2,409 (99.7%) were matched to controls. Prevalence of atopic dermatitis (relative risk [RR] = 2.571; 95% confidence interval [CI] = 2.356-2.806), depression (RR = 1.705; 95% CI = 1.566-1.856), anxiety (RR = 1.540; 95% CI = 1.407-1.686), coronary heart disease (RR = 1.575; 95% CI = 1.388-1.787), chronic kidney disease (RR = 1.529; 95% CI = 1.329-1.759), and type 2 diabetes mellitus (RR = 1.836; 95% CI = 1.597-2.111) was significantly higher for patients with PN. Subsequent risk of atopic dermatitis (hazard ratio = 6.58; 95% CI = 5.17- 8.37), depression (hazard ratio = 1.61; 95% CI = 1.30-1.99), and coronary heart disease (hazard ratio = 1.37; 95% CI = 1.09-1.74) were significantly increased. Resource utilization was increased in all settings: incidence rate ratio = 1.48 (95% CI = 1.47-1.49) for primary care, incident rate ratio = 1.80 (95% CI = 1.75-1.85) for inpatients, incident rate ratio = 2.15 (95% CI = 2.13-2.18) for outpatients, and incidence rate ratio = 1.32 (95% CI = 1.27-1.36) for accident and emergency. Respective cost ratios were 1.78 (95% CI = 1.67-1.90), 1.52 (95% CI = 1.20-1.94), 2.34 (95% CI = 2.13-2.58), and 1.55 (95% CI = 1.33-1.80). Total primary and secondary healthcare costs were £2,531 versus £1,333, a cost ratio of 1.62 (95% CI = 1.36-1.94). The adjusted hazard ratio for mortality was 1.37 (95% CI = 1.14-1.66). Patients with PN had significantly increased rates of comorbidity, healthcare resources utilization, and mortality compared with matched controls.